HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP DENGAN PEMAKAIAN ALAT PELINDUNG DIRI (APD) PADA PEMANEN KELAPA SAWIT DI DESA RANTAU RASAU TAHUN 2021 - Yulfi Okta Juria; Ahmad Husaini; Renny Lstiawaty (Jurnal Inovasi Penelitian, 2023)
The use of personal protective equipment is the final stage of the method of controlling occupational accidents and occupational diseases. Oil palm farmers in Rantau Rasau Village on average harvesters do not use personal protective equipment that must be worn while working such as: helmets, gloves, and boots. The purpose of the study was to determine the relationship between knowledge and attitude with the use of personal protective equipment. The research design used was cross sectional. This research was conducted in Rantau Rasau Village on August 31 to September 3, 2021. The research sample was 46 oil palm farmers in Rantau Rasau Village. The sample size was determined by saturated sampling. The research instrument was a questionnaire. Data collection techniques by interviewing respondents. The collected data were analyzed univariately and bivariately using the chi square test. A total of 50.0% of respondents had poor behavior in the use of personal protective equipment, 63.0% of respondents had good knowledge and 56.5% of respondents had good attitudes. The results of bivariate analysis show that there is a relationship between knowledge (p = 0.002) and attitude (p = 0.037) with the use of personal protective equipment on oil palm farmers in Rantau Rasau Village in 2021. It is expected that oil palm farmers always use personal protective equipment when working which serves to reduce the impact of accidents on labor from accidents that may occur in the workplace